2015
DOI: 10.1016/j.vetmic.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental stressors result in increased viral load and further reduction of production parameters in pigs experimentally infected with PCV2b

Abstract: HighlightsEnvironmental stress increases viral load of PCV2b in serum and tissue.Environmental stress exacerbates PCV2b induced weight loss.Environmental stress and PCV2b reduce ADG and impact negatively on FCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Morbidity varies drastically, from subclinical infections and reduced growth performance to increased mortality. Host genetics, immunity, environmental stressors and secondary pathogens are all factors which can impact clinical outcome following PRRSV or PCV2 infections (Boddicker et al, 2012;Chand et al, 2012;Opriessnig and Halbur, 2012;Patterson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity varies drastically, from subclinical infections and reduced growth performance to increased mortality. Host genetics, immunity, environmental stressors and secondary pathogens are all factors which can impact clinical outcome following PRRSV or PCV2 infections (Boddicker et al, 2012;Chand et al, 2012;Opriessnig and Halbur, 2012;Patterson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These are often employed to achieve a systemic IgG as well as mucosal IgA response following antigen uptake by micro-fold (M) cells [5] , [6] . Vaccines administered via the oral route cause in general less stress and associated immune-suppression for the recipient [7] , both of which are risk factor for developing PCVAD [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on available information, it has been shown that several infectious cofactors and noninfectious conditions such as concurrent infection with other pathogens [103, 104], host genetic make-up [105], and management practices [106] are crucial for disease progression to PCVAD. Consequently, infections with PCV2 have been regarded as multifactorial at the instances of other underlying cofactors that exacerbate infection with the viral pathogens resulting in the clinical disease manifestations.…”
Section: Porcine Circovirus Type 2 (Pcv2)mentioning
confidence: 99%
“…[114], E. coli [115], and Metastrongylus elongatus [116]. The noninfectious cofactors include the genetic background of the pig, high stocking density, and prevailing environmental conditions such as temperature fluctuation within the pen [106]. …”
Section: Porcine Circovirus Type 2 (Pcv2)mentioning
confidence: 99%